Ligno-Cellulose Degrading and Antimicrobial Activities of Selected Strains of Actinomycetes Isolated From Malaysian Rainforest Soils - Tang, Sui Yan (2006)
Eighteen soil samples were collected from the tropical forest floor at Kuala Tahan National Park, Pahang. Soil Water content and soil pH were determined. Isolation of actinomycetes bacteria isolates was accomplished via multi-stage Dispersion and Differential Centrifugation (DDC) technique and total of 227 isolates were obtained and maintained on Starch-Casein Nitrate (SCN) medium. All soil samples gave high colony forming units (C.F.U.) counts when grown on medium of pH 7.0 (1.0-6.7 x 106) as compared to pH 5.0 (0.4-2.2 x 106). All isolates showed very diverse colony morphologies. Of 227 isolates, 24.67% (56/227) showed Xylanase activity, 28.63% (65/227) with Cellulase activity and 7.93% (18/227) for Galacto-mannanase. Antagonistic activities were also observed against plant pathogens of Xanthomonas campestris at 12.78% (29/227), Ralstonia solanacearum at 39.65% (90/227), Erwinia crysanthemi 0% (0/227) and Pantoea stewartii at 16.30% (37/227). Whereas in gram negative food pathogens of Salmonella typhimurium at 0.88% (2/227) and Vibrio parahaemolyticus at 6.61% (15/227). Antagonistic against gram positive food pathogens of Staphylococcus aureus was at 21.59% (49/227) and Listeria monocytogenes at 6.61% (15/227). Ten actinomycetes isolates (A3, C1, G2, G3, G4, G10, I15, L8, O15 and P5) were selected based on their bioactive compound profiles and subjected to microscopic studies, metabolic finger printing using BIOLOG system and partial 16S rDNA analysis. Significant and diverse differences between all 10 selected isolates were observed via BIOLOG carbon utilization profiling and cell morphology under light microscopy. Isolate G4 and O15 were identified as members of genus Kitasatospora while the other eight isolates belong to genus Streptomyces using 16S rDNA sequence analysis and light microscopy. The ability to produce extracellular enzymes and antagonism activity against plant pathogens indicated that the 10 selected isolates have potential to be consortia of microorganisms as inoculum in agrowaste composting such as oil palm’s empty fruit bunch. The inoculum not only increases the nutrient value in compost materials but also has advantage to control plant disease in soil ecosystem.